Distribution of Iron on FCC Catalyst and Its Effect on Catalyst Performance - Liao, Yitao; Liu, Tao; Du, Xiaohui; Gao, Xionghou (Frontiers in Chemistry, 2021)
The effects of different iron contamination content on the formation of iron nodules and the performance of FCC catalyst have been studied by cyclic deactivation treatment using iron naphthenate. The catalysts were characterized by X-ray diffraction, N2 adsorption-desorption and SEM. The catalysts performance was evaluated by Advanced Cracking Evaluation device. It has been found that there will be obvious nodulation on the catalyst when the iron concentration exceeds 7400 μg/g. With the iron deposition from 53 μg/g to 11690 μg/g, the crystal structure of the zeolite will not be destroyed by iron. The surface area and pore volume of catalyst decreased significantly, the surface area decreased from 125.3 m2/g to 91.0 m2/g and the pore volume decreased from 0.21 cm3/g to 0.16 cm3/g. The studies also showed that the increase of iron deposition will lead to the decrease of catalytic reaction efficiency. With the iron deposition from 53 μg/g to 11690 μg/g, the conversion decreased by 4.83%. Under the same conversion of 78%, bottoms yield and coke yield increased by 2.15% and 1.31%, while gasoline yield and LCO yield decreased by 2.59%, and 2.16%. The real state of industrial iron contaminated equilibrium catalyst can be mimicked by using cyclic deactivation method.